SciFi detector and associated method for real‐time determination of profile and output factor for small fields in stereotactic radiotherapy. Issue 4 (30th January 2020) - Pittet, P.; Esteves, J.; Galvan, J.‐M.; Lu, G.‐N.; Blanc, F.; Haefeli, G.; Hopchev, P.; Rit, S.; Desbat, L.; Ribouton, J.; Jalade, P.
Abstract : Purpose: For determining small‐field profile and output factor during stereotactic radiotherapy quality assurance (QA) procedures, we propose a novel system based on the scintillating fiber (SciFi) detector with output image acquisition and processing to allow real‐time monitoring of profile and output factor. Materials and methods: The employed detector is a SciFi detector made of tissue‐equivalent scintillating plastic fibers arranged in 6‐layer fiber ribbons with a fiber pitch of 275 μm in each layer. The scintillating signal at the detector output is acquired by a sCMOS (scientific complementary metal–oxide–semiconductor) camera and represents the projected field profile along the fibers axis. An iterative reconstruction method of the field from its projected profile based on a priori knowledge of some features of the radiation field defined by the stereotactic cones is suggested. The detector with implemented data processing has been tested in clinical conditions, for determining beam profiles and output factors, using cone collimators of different sizes from 4 to 15 mm diameter. The detector under test was placed at 1.4 cm depth and 98.6 cm source to surface distance (SSD) in a water‐equivalent phantom and irradiated by a 6 MV photon beam. Results: The reconstructed field profiles obtained from the detector are coherent with data from EBT3 radiochromic films, with differences within ±0.32 mm for both the FWHM and the penumbra region. For real‐time determination of the field output factor, the measured data are also in good agreement with data independently determined by the French Institute for Radiological Protection and Nuclear Safety (IRSN) based on radiochromic films and thermoluminescent 1 × 1 mm 2 micro‐cubes dosimeters (TLD). The differences are within ±1.6% for all the tested cone sizes. Conclusions: We propose and have tested a SciFi plastic scintillating detector with an optimized signal processing method to characterize small fields defined by cone collimators. It allows the determination of key field parameters such as full width at half maximum (FWHM) and field output factors. The results are consistent with those independently measured using TLD and radiochromic films. As the SciFi detector does not require a correction factor, it is in line with the International Atomic Energy Agency (IAEA) and the American Association of Physicists in Medicine (AAPM) TRS‐483 recommendations, and can be suitable for online QA of small radiation fields used in photon beam radiotherapy, and is compatible with MRI‐LINAC.